2016
DOI: 10.17957/ijab/15.0218
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Regulation of Lipid Synthesis in the Developing Seeds of Two Biodiesel Tree Species, Jatropha and Vernicia

Abstract: The fatty acid compositions of Jatropha oil and Vernicia oil are strikingly different, which leads to a great difference in combustion performance, low temperature performance and oxidation stability. A comparative transcriptomic study was made in Vernicia and Jatropha, with a focus on the gene regulation of differential oil accumulation process. Transcriptome sequencing was conducted with seeds at the initial-and fast-stage of oil accumulation from both. More than 24 billion bases of cDNA sequence were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A contains some compounds that can be used in the pharmaceutical industry. 9,12-Octadecadienoic acid (Z, Z) - (3.49%) is a lipid-lowering drug and can also be used as a raw material for the treatment of atherosclerosis (Yang et al, 2016). beta.-Sitosterol (0.50%) has the functions of lowering cholesterol, relieving cough, eliminating phlegm, inhibiting tumor and repairing tissue.…”
Section: Resultsmentioning
confidence: 99%
“…A contains some compounds that can be used in the pharmaceutical industry. 9,12-Octadecadienoic acid (Z, Z) - (3.49%) is a lipid-lowering drug and can also be used as a raw material for the treatment of atherosclerosis (Yang et al, 2016). beta.-Sitosterol (0.50%) has the functions of lowering cholesterol, relieving cough, eliminating phlegm, inhibiting tumor and repairing tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are at least four types of DGATs [ 38 , 39 ], type 1 and type 2 DGATs are reported to contribute to TAG synthesis in most plant species. In J. curcas , three DGAT genes, JcDGAT1 , JcDGAT2 , and JcDGAT3 , have been identified [ 37 , 40 ], in which JcDGAT1 and JcDGAT2 have been proven to affect oil accumulation in Arabidopsis and tobacco [ 34 , 35 ]. In addition, virus-induced gene silencing of a transcription factor JcMYB1 in J. curcas leaves down-regulated the expression of JcDGAT1 , resulting in a reduction in the lipid content [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researches have confirmed that species-specific fatty acid desaturases (FAD2, FADX, FAH12, etc. ), oleocins, and phospholipid:diacylglycerol acyl transferase (PDAT) proteins are involved in or regulating fatty acid compositions in seeds of Vernicia and Jatropha (Yang et al, 2016).…”
Section: Tag Biosynthesis Pathway and Candidate Genes For Metabolic Ementioning
confidence: 99%